Organization : a guide to problems and practice - Child, John, 1940- (Paul Chapman, 1984)
This textbook provides a clear and readable introduction to the subject. It deals with organizational design, its contribution to performance, and the problems and issues involved in organizational change. This text assumes little academic knowledge, and some familiarity with work in organizations. It is of real use to decision makers, and to those in management education, both teachers and students.